Impact of service life and system boundaries on life cycle assessment of sustainable concrete mixes - Pradhan, Subhasis (2022)
Partial substitution of cement/clinker in concrete mix helps reduce its environmental impact. The supplementary cementitious materials such as fly ash and ground granulated blast furnace slag (GGBS), and limestone calcined clay concrete (LC3) are thus been exploited without affecting the short-term performance of concrete. The long-term performance of concrete largely affects the service life of a structure and consequently the environmental impact during the service period. Hence, a comparative life cycle assessment study of four concrete mixes (controlled, fly ash blended (FA30), GGBS blended (GGBS50) and LC3) considering cradle-to-gate and cradle-to-grave system boundaries is conducted for the scenario in Singapore. The chloride resistance of these concrete mixtures is considered for service life estimation as it is the major cause for corrosion of the reinforcement. The uncertainty study reflects the dependence of service life on threshold chloride content. The service life is in the order of LC3 > FA30 > GGBS50 > controlled mix. LC3 and controlled concrete exhibit minimum and maximum environmental impact, respectively irrespective of system boundary. In cradle-to-gate system boundary, GGBS50 exhibits lesser environmental impact than FA30 excluding abiotic depletion, human toxicity, freshwater aquatic ecotoxicity and marine aquatic ecotoxicity impact categories owing to higher cement substitution level. However, the consideration of service life in cradle-to-grave system boundary resulted in lesser environmental impact for FA30 than GGBS50 in all impact categories (apart from acidification, GWP and terrestrial ecotoxicity), owing to the fewer repair cycles and subsequent utilization of concrete.